Spectacles of truth in classical Greek philosophy theoria in its cultural context - Nightingale, Andrea Wilson (Cambridge University Press, 2004)
In an effort to conceptualize and legitimize theoretical philosophy, the Greek philosophers turned to a venerable cultural practice: theoria (state pilgrimage). In this traditional practice, an individual journeyed abroad to officially witness sacralized spectacles. This book examines the philosophic appropriations and transformations of the practice of theoria.